The Energy Strategy of the Russian Federation: the transformation and implementation issues - K. N. Zasipkin (Путеводитель предпринимателя)
The comparison of Russia’s energy strategy up to 2030 and up to 2035 was made in the article. The basic directions of transformation of Russia’s energy strategy were analyzed. The necessity of creating a high-performance workplaces in the energy sector to ensure the implementation of innovative processes was described.